Late blight resistance of Ecuadorian potato landraces: field evaluation and farmer’s perception - Monteros-Altamirano, Álvaro; Delgado, Ricardo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Late blight, caused by Phytophthora infestans (Mont.) de Bary, is one of the most devastating diseases of potato world-wide. A field experiment, in a location under high P. infestans pressure, was carried out in Ecuador to assess resistance or susceptibility to late blight of 31 potato landraces collected in Carchi, Chimborazo and Loja. Resistant commercial varieties (I-Fripapa) and a susceptible (Superchola) were included as references. Based on the Area Under the Disease Progress Curve (AUDPC) three categories were scored: resistant, intermediate and susceptible. The landraces under study showed different responses to late blight in the experimental field. Only, five landraces showed the best field resistance: Uva, Chaucha roja, Guata amarilla, Coneja and Chaucha ratona. Additionally, a survey to 150 farmers growing potato landraces in these three provinces identified the main diseases affecting their potatoes. Informal conversations with these farmers both during the collections and during farmer meetings provided additional information regarding late blight and their perception of landrace resistance. Similar to farmers growing commercial varieties also farmers currently cultivating landraces consider late blight as the main disease in their potatoes. Probably the broad crop diversity on their farms and the planting of potato landrace mixtures reduces the late blight severity effects within their potato fields. Possible strategies to improve late blight resistance in potato in Ecuador could include the identification of accessions with resistance among local landraces, wild potato relatives and/or the introduction of new sources of resistance from other origins.